Factors associated with parental resolution of a child's autism diagnosis: A systematic review - Naicker, Vrinda V.; Bury, Simon M.; Hedley, Darren (Frontiers in Psychiatry, 2023)
Background: Receiving a child’s autism diagnosis can be particularly stressful for parents. In other significant childhood diagnosis (e.g., cerebral palsy, diabetes), the degree to which parents adjust to a) their child’s diagnosis and b) their changes in expectations concerning their child’s development and capacity, collectively referred to as resolution to diagnosis, has been associated with improved outcomes including facilitating parent-child relationships and improved parental wellbeing. Given potential benefits to parent and child, and the heterogenous nature of autism, examining the unique factors associated with resolution to diagnosis is important. In this systematic review we identified factors that support or inhibit parental resolution to their child receiving a diagnosis of autism. Methods: We completed a systematic review following PRISMA guidelines of peer-reviewed studies from 2017 that investigated parental resolution or acceptance of an autism diagnosis. Papers including ‘acceptance’ needed to encompass both accepting the diagnosis and the implications regarding the child’s abilities. We searched six databases (Scopus, Web of Science, MEDLINE, PsycINFO, ProQuest), with additional papers located following review of reference lists. Results: Fourteen papers with 592 participants that investigated parental resolution or acceptance of autism diagnosis, were included. We identified six common factors that facilitate or inhibit parental resolution and acceptance of an autism diagnosis including: symptom severity; religion, belief, and culture; knowledge and uncertainty; negative emotions (i.e., denial, shame, guilt); positive emotions and support. Greater resolution was associated with improved ‘attunement and insightfulness’ in the child parent relationship. Limitation: The review was limited by the small number of studies meeting inclusion criteria. Second, the quality of included studies was mixed, with over half of the studies being qualitative and only one randomized control trial (RCT) identified. Conclusion: Parental resolution can have an impact on parent’s perception of their child’s capabilities and impact the parent-child relationship. We identified six categories that aid in inhibiting or promoting resolution to diagnosis. Despite taking a broad approach on the definition of resolution, the low number of studies identified in the review indicates a need for more research in this area.